Flora diversity of the Bai Tu Long national park (Quang Ninh province) - Phuong, Vu Xuan; Huyen, Duong Duc; Cuong, Nguyen The (Academia Journal of Biology, 2014)
The Baitulong national park (BTLNP) in the Quangninh province was established by the decision No. 85/2001 Q§-TTg of the Prime Minister in 2001. Before that, some expeditions to investigate the flora of the BTLNP had been carried out. About 117 families with 337 genera, 494 vascular plant species were recorded in September 2000. Some other investigations have been performed in two years 2005-2006. Preliminary results showed that the flora of the BTLNP is very rich and diversified. A checklist with 780 species belonging to 468 genera of 135 families of 5 vascular plant phyla has been done. Almost of them belonged to the phylum Magnoliophyta (114 families, 438 genera, 729 species). Information of valuable, rare and endangered species had been reported. Among total 18 valuable, rare or endangered species in the park, 10 species was recorded in the Red Data Book (1996), and 10 species existed in the annexes IA or IIA of the Governmental Decree 32/2006/ND/CP (March 2006). There were also 557 useful species in the BTLNP. Among them, 431 species have been used as medicinal plants. Especially, Ilex kaushue S. J. Hu had been found for the first time in the BTLNP. This species and some others such as Morinda officinalis How, Ardisia silvestris Lour needed to be protected, propagated and developed. Besides, 116 species were listed as timber trees (Erythrophleum fordii Oliv., Hopea chinensis (Merr.) Hand.-Mazz., Vatica odorata (Griff.) Symingt., Bruguiera gymnorhiza (L.) Savigny, Rhizophora stylosa Griff.). Statistics showed that other groups of useful plants existed in the BTLNP. Groups of edible fruit and nut plants consist 44 species, vegetable plants 33 species, essential oil and fat plants 27 species, fibred plants 20 species.